FRI0343 EFFICACY AND SAFETY OF FILGOTINIB, A SELECTIVE JANUS KINASE 1 INHIBITOR, IN PATIENTS WITH ACTIVE PSORIATIC ARTHRITIS: SUBGROUP ANALYSES FROM A RANDOMIZED, PLACEBO-CONTROLLED, PHASE 2 TRIAL (EQUATOR). (2nd June 2020) - Helliwell, P.; Van den Bosch, F.; Coates, L. C.; Gladman, D. D.; Tasset, C.; Meuleners, L.; Gilles, L.; Gheyle, L.; Trivedi, M.; Alani, M.; Besuyen, R.; Mease, P. J.
Abstract : Background: Treatment with the oral selective Janus kinase 1 inhibitor filgotinib was associated with rapid and significant improvements in multiple domains of active psoriatic arthritis versus placebo in the 16-week Phase 2, multicenter, double-blind, randomized EQUATOR trial (NCT03101670 ). 1 A significantly greater proportion of patients receiving filgotinib, versus placebo, achieved the primary endpoint of 20% improvement in American College of Rheumatology (ACR) 20 response at Week 16 (80% vs 33%, respectively). 1 Objectives: The aim of this predefined analysis was to evaluate the consistency of the response to filgotinib across predefined relevant subpopulations participating in the EQUATOR trial. Methods: In EQUATOR, patients with active psoriatic arthritis were treated with filgotinib 200 mg (n=65) or placebo (n=66) once daily for 16 weeks. Key clinical endpoints, including ACR20 and ACR50 (50% improvement) response rates, Psoriatic Arthritis Disease Activity Score (PASDAS), and Disease Activity Index for Psoriatic Arthritis (DAPSA) were evaluated according to the following baseline characteristics: sex, body mass index, disease duration, baseline disease severity, concurrent use of disease-modifying antirheumatic drug(s), and prior exposure to tumor necrosis factor inhibitor(s). For PASDAS and DAPSA scores, statistical analysis of changes from baseline was performed using analysis of covariance with factors for treatment, randomization stratification, subgroup, and an interaction between treatment and subgroup. Least-squares (LS) mean difference between treatment arms and the corresponding 95% confidence intervals (CI) were calculated. For ACR20 and ACR50 response rates, statistical analysis used the point estimate and corresponding 95% CI, based on the Newcombe method. Results: Sixty patients (92%) in the filgotinib group and 64 (97%) in the placebo group completed the study. The total number of patients in each subpopulation ranged from 18 to 104 (Figure 1 ). Differences in the proportions of patients achieving ACR20 consistently favored filgotinib, compared with placebo, across all subgroups (Figure 1 ); all differences reached statistical significance. Similarly, differences in the proportions of ACR50 responders and LS mean treatment differences for PASDAS and DAPSA consistently favored filgotinib, reaching statistical significance in most subgroups. No clinically relevant differences in the effect of filgotinib were observed across subgroups. Filgotinib was generally well tolerated and no new safety signals were identified. Conclusion: In the 16-week EQUATOR trial, the effects of filgotinib on key efficacy endpoints were generally consistent across a range of subgroups based on patient, disease, and treatment characteristics. References: [1]Mease P, et al. Lancet 2018;392:2367–77. Acknowledgments: The EQUATOR trial was sponsored by Galapagos NV and co-funded by Galapagos NV and Gilead Sciences. Medical writing support was provided by Hannah Mace MPharmacol, CMPP (Aspire Scientific Ltd, Bollington, UK) and funded by Galapagos NV (Mechelen, Belgium). Disclosure of Interests: Philip Helliwell: None declared, Filip van den Bosch Consultant of: AbbVie, Celgene Corporation, Eli Lilly, Galapagos, Janssen, Novartis, Pfizer, and UCB, Speakers bureau: AbbVie, Celgene Corporation, Eli Lilly, Galapagos, Janssen, Novartis, Pfizer, and UCB, Laura C Coates: None declared, Dafna D Gladman Grant/research support from: AbbVie, Amgen Inc., BMS, Celgene Corporation, Janssen, Novartis, Pfizer, UCB – grant/research support, Consultant of: AbbVie, Amgen Inc., BMS, Celgene Corporation, Janssen, Novartis, Pfizer, UCB – consultant, Chantal Tasset Shareholder of: Galapagos (share/warrant holder), Employee of: Galapagos, Luc Meuleners Employee of: Galapagos, Leen Gilles Consultant of: Galapagos, Lien Gheyle Employee of: Galapagos, Mona Trivedi Shareholder of: Amgen and Gilead Sciences, Employee of: Gilead Sciences, Muhsen Alani Employee of: Gilead Sciences, Robin Besuyen Shareholder of: Galapagos, Employee of: Galapagos, Philip J Mease Grant/research support from: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – grant/research support, Consultant of: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – consultant, Speakers bureau: Abbott, Amgen, Biogen Idec, BMS, Eli Lilly, Genentech, Janssen, Pfizer, UCB – speakers bureau